A Study of Water Phantom Homogeneity from DICOM CT-Images Based on ImageJ (Journal of Nuclear Technology in Applied Science, 2020)
The real data for water phantom have complex variations in the distribution of CT (Computed Tomography) number values for each slice. Thus, the accuracy of dose calculation on a homogeneous medium becomes very important to be reviewed. This study aims to review the distribution of CT numbers (in Hounsfield Units, HU) in a water phantom homogeneity determination. The water phantom was of the IBA dose 1 type, with dimensions of 40 cm x 35 cm x 35 cm. The image dimensions were 500 x 500 mm2 with a 1 mm pixel thickness, and 512 x 512 matrix size at image reconstruction. The overall division of water phantom slices was taken from the z-direction or parallel to the patient table into 441 slices. Water phantom homogeneity determination consisted of scanning procedures and image processing. Based on the analysis of the CT number distribution of all slices, the accepted slices were composed of 350 water and 18 acrylic slices. Furthermore, 42 anomaly slices were identified from the calculation of mean and standard deviation. The ROI (Region of Interest) was also considered, reducing water CT number to 53.06 HU. Based on this study, a method for homogeneity determination from the distribution of CT numbers in water phantom IBA Dose 1 was developed.
Keywords: Water phantom; CT Number; (HU) distribution; homogeneity; ImageJ